2012
DOI: 10.1002/cncr.27555
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of soft tissue sarcoma and beyond

Abstract: BACKGROUND:The objectives of this study were to measure the incidence of sarcomas, including viscerally sited tumors that are not reported in cancer statistics, and to draw explanatory clues from a large and reliable sarcoma incidence data set. METHODS: Cases of sarcomas regardless of primary site (except bone and joints) were collected during 2 years in 3 European regions totaling approximately 26,000,000 person-years. The sources used were pathology reports and hospital discharges forms. Diagnoses were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
84
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(94 citation statements)
references
References 29 publications
8
84
0
2
Order By: Relevance
“…In contrast, few other European studies, studies from the United Kingdom and the United States report a higher incidence of STS in males 15, for example, Toro et al. (U.S.A.) 2 and a regional study based in France and Italy 17. Hence, due to inconsistencies in results from various studies, clear gender predilection of STS cannot be obtained.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, few other European studies, studies from the United Kingdom and the United States report a higher incidence of STS in males 15, for example, Toro et al. (U.S.A.) 2 and a regional study based in France and Italy 17. Hence, due to inconsistencies in results from various studies, clear gender predilection of STS cannot be obtained.…”
Section: Discussionmentioning
confidence: 96%
“…This incidence rate falls at the high end of the range of published international incidence rate (1.8 and 5.0 per 100,000 per year). The ASR in Ireland is similar to the United Kingdom but differs from other countries of central Europe and the United States 2, 4, 15, 17. The inclusion criteria, number of cases, classification and typing standards of STS may differ for each country and over various time periods.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the molecular mechanism of dedifferentiation and no genetic alteration has been identified as contributing to this process yet. Recently, it has been suggested that the number of dedifferentiation events in LPS could be underestimated and that actually DDLPS might be the most common histological subtype [6]. MLPS, the third subtype of LPS, is distinguished by the presence of a specific translocation t(12;16) [7] or t(12;22) [8] that is the key genetic aberration, extremely helpful in differential diagnosis between MLPS and myxofibrosarcomas [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract, with a mean annual incidence of 10–15 cases per million people, affecting mainly older individuals at a median age of 55–65 years [14]. Radical surgery is the treatment of choice in primary resectable GISTs, but almost all GISTs are associated with a risk of recurrence, and approximately 40–50 % of patients with potentially curative resections develop recurrent or metastatic disease [5, 6].…”
Section: Introductionmentioning
confidence: 99%